Rice blast disease - IRRI (IRRI, 1994)
The principal focus of the conference was to explore approaches no manage rice blast by intergrating basic knowledge about the disease with developments in rice technology, biological control, breeding for disease resistance, and indigenous agricultural knowledge. With recent progress in rice and fungal transformation and the mapping and cloning of rice genes, it is reasonable to consider that biotechnology will make major contributions towards controlling this disease.